Structure and Meaning in English : a Guide for Teachers. - Kennedy, Graeme (Taylor and Francis, 2014)
Structure and Meaning in English is designed to help teachers of English develop an understanding of those aspects of English which are especially relevant for learners who speak other languages. Using corpus research, Graeme Kennedy cuts to the heart of what is important in the teaching of English. The book provides pedagogically- relevant information about English at the levels of sounds, words, sentences and texts. It draws attention to those linguistic items and processes which research has shown are typically hard for learners and which lead to errors. Each chapter.